The carbon footprint of construction industry: A review of direct and indirect emission - Yahaya Hassan LABARAN; Vivek Shankar MATHUR; Mahmoud Murtala FAROUQ (Journal of Sustainable Construction Materials and Technologies, 2021)
The construction industry is considered to be among the major sectors that contribute significantly toward the emission of GHGs in our environment, which have a major effect on the climate change, and is approximately responsible for about 19 percent of the overall GHG emission globally, rendering it a pollution hotspot requiring urgent mitigation measures. Unfortunately, there are few studies on this subject to help construction companies meet their low-carbon targets. As a result, this paper reviewed the contributions of researchers across the globe towards carbon dioxide and other GHGs emissions from the industry. After a systematic review of some of these studies, it was found that the majority of researchers focused primarily on a specific feature of the construction industry, a case study of a particular country/city or region, using the Life Cycle Assessment approach. And, even those who have studied similar aspects such as cement or steel, have all used different methodologies, units, and techniques of reporting. As such, a comparison between the findings of the literature is unrealistic. Despite this, the scope of the emission from the construction industry is remarkably clear, and the carbon findings can be found throughout the literature.